Hubungan CEO Overconfidence dengan Penghindaran Pajak - Nurul Hidhayana; Novrys Suhardianto (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2021)
The purpose of this study was to analyze the relationship between CEO overconfidence and tax avoidance. This study uses overinvestment to measure the level of overconfidence of a company CEO. The tax avoidance is measured by the Effective Tax Ratio (ETR). This study uses 567 observations from non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period and uses STATA 14.0 software to analyze the data. The results of the analysis show that CEO overconfidence has a positive relationship with tax avoidance. Companies that have CEO overconfidence tend to be involved in regulating corporate taxes which leads to tax avoidance activities. Thus, this study succeeded in proving that the more overconfident a CEO is, the more aggressive the tax avoidance will be.